Statistical analysis of flood risk factors = Analiza statystyczna czynników ryzyka powodziowego - Asani, Anna; Kołodziejczyk, Urszula (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The durability of hydrotechnical structures, especially flood embankments, depends largely on the correct identification of natural phenomena occurring in both the embankment body and the foundation. Such a phenomenon - particularly important from a flood protection viewpoint ? is water filtration through the embankment.
Keywords: wały przeciwpowodziowe; lubuski odcinek Odry; czynniki ryzyka powodziowego; analiza statystyczna; Lubuskie Region; Oder river; flood protection; statistical analysis